THE REBORN OF EXCLUSIVE BREASTFEEDING METHOD: ANTENATAL BREAST EXPRESSION (ABE) : A LITERATURE REVIEW - Aida Amalia Nur Ramadhian; Sheyla Najwatul Maula; Ulfah Musdalifah (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Antenatal Breast Expression (ABE) is believed as a potential method to improve colostrum secretion upon labor which the complex content of colostrum can prevent the infection, obesity, diabetes and malignant diseases among newborns. This study aims to to analyze and provide detailed description on the practice of ABE to support the exclusive breastfeeding program.Method: Literature review was conducted in this study using the PRISMA protocol guidelines. Data were obtained by accessing electronic resources from Science Direct, Sage Publications, PubMed, and Google Scholar with ‘antenatal breast expression’, ‘antenatal milk expression’, and ‘colostrum secretion’ as the keywords. The articles analyzed in this study were published from 2009 to 2018 and written in English.Results: There were eighty articles recorded, of which eight articles were included in the systematic review. ABE was performed every day when the pregnancy reaches 37 weeks. The average secretion time of this practice was 5-10 minutes each for 1-4 times a day, preferably during showers. The ABE affected babies in that it allowed them to get timely nutritional intake in order to stabilize blood sugar and to prevent icterus. Even though the practice of ABE was viewed differently among women of reproductive age, it nonetheless helped to improve self-confidence among breastfeeding mothers, to reduce transition interval from Early Initiation of Breastfeeding (EIB) to full lactation, to improve lactation performance, and to induce natural delivery. However, it was not yet widely practiced as it was still under consideration by the International Board Certified Lactation Consultant (IBCLC).Conclusion: ABE has proven to benefit both mothers and babies, despite existing pros and cons. Therefore, there is a need for more systematic review using other keywords and methods on the safety and efficacy of ABE practice to ensure its benefit for breastfeeding.